CRITICAL PSYCHOLOGY IN SOUTH AFRICA: APPLICATIONS, LIMITATIONS, POSSIBILITIES - Hook, Derek (PINS-Psychology in Society, 2026)
Critical psychology - to my mind at least - revolves around one central (and fairly basic) tenet - that psychology is a political tool. Bulhan makes this point at the beginning of his (1985) Frantz Fanon and the psychology of oppression, by means of a pointed comparison between the careers of Fanon and Verwoed: "The two men ... were psychologists who put to practice their profession in ways that made history and affected the lives of millions ... Verwoed was a staunch white supremacist, a Nazi sympathizer, an avowed anti-Semite, and a leading architect of apartheid ... Fanon, in contrast, was a relentless champion of social justice who, when barely 17 ... volunteered for the forces attempting the liberation of France from Nazi liberation" (p3). This is an important contribution to the socio-political history of psychology in that it leaves little doubt as to the political utility of psychology, as either instrument of oppression, or as potentially enabling means of progressive politics. One word of caution though: this comparison should not be taken to imply that psychology's involvement in politics is merely circumstantial, arbitrary, opportunistic. As Bulhan (1985) goes on to make abundantly clear, and as critical psychology should assert whenever possible, psychology is always - even in its most everyday and mundane forms - political. In many ways in fact, and depending on the radicalism of one's critique, this may be not only psychology's most important function - generating and cementing kinds of politics - but also the motivating objective behind its initial emergence as a disciplinary practice. [In this respect see particularly Foucault (1977) and Rose (1991, 1995), but also Cushman (1990, 1992)]. Just as critical psychology endeavours to "play up" the very political nature of psychology, so the traditional, or mainstream practices and applications of psychology have, historically, attempted to do just the opposite, to "play down• this nature. Hence Hayes' (1989) understatement: "The study of ideology has not been a central issue in the history of psychology" (p84). The link here - between psychology's omission of ideology as an important focus of study, and psychology's own immanently (yet elided) political nature - may not yet seem quite clear. Hayes' further comments help articulate this link. There could, Hayes (1989) claims, be at least two possible ways of addressing the issue of ideology in psychology, one which at basis is critical, another which at basis is substanuve: "The critical dimension refers to the knowledge claims and the ontological status of psychology as a science ... The substantive dimension refers to the operations of ideology at the level of the individual" (Hayes, 1989:84). Whereas the critical dimension would interrogate psychology across the science/ideology dialectic - engaging psychology as a particular politics of knowledge - the substantive dimension would examine the theoretical and formal constitution of the subject of psychological theory and research - engaging psychology as a particular politics of subjectivity. It is on these bases that Hayes (1989:84) makes the appeal that "[T]he wh·ole question and place of politics in psychology ... certainly ... justifies a more coherent and rigorous analysis… "